Circ-USP9X interacts with EIF4A3 to promote endothelial cell pyroptosis by regulating GSDMD stability in atherosclerosis - Shengkai Xu; Yishan Ge; Xuebin Wang; Wei Yin; Xiaoqing Zhu; Jie Wang; Shigang Qiao (Clinical and Experimental Hypertension, 2023)
Endothelial pyroptosis is a pathological mechanism of atherosclerosis (AS). Circular RNAs (circRNAs) are vital in AS progression by regulating endothelial cell functions. The study aimed to explore whether circ-USP9× regulated pyroptosis of endothelial cell to involve in AS development and the molecular mechanism. Pyroptosis was determined using lactate dehydrogenase (LDH) assay, enzyme linked immunosorbent assay (ELISA), flow cytometry, propidium iodide (PI) staining assay, and western blot. The mechanism of circ-USP9× was determined using RNA pull-down and RNA binding protein immunoprecipitation (RIP) assays. Results showed that circ-USP9× was upregulated in AS and oxidized low-density lipoprotein (ox-LDL)-treated human umbilical vein endothelial cells (HUVECs). Knockdown of circ-USP9× suppressed ox-LDL induced pyroptosis of HUVECs. Mechanically, circ-USP9× could bind to EIF4A3 in the cytoplasm. Moreover, EIF4A3 was bound to GSDMD and further affects GSDMD stability. Overexpression of EIF4A3 rescued cell pyroptosis induced by circ-USP9× depletion. In short, circ-USP9× interacted with EIF4A3 to enhance GSDMD stability, thus further promoting ox-LDL-induced pyroptosis of HUVECs. These findings suggested that circ-USP9× participates in AS progression and may be a potential therapeutic target for AS.